(untitled) (Jurnal Bahasa, 2024)
Speech acts are utterances that convey meaning depending on specific contexts. This study was conducted to analyze the speech acts in the film ‘Adiwiraku’ using Searle’s Speech Act Theory. The theory categorizes speech acts into five types, which are directives, assertives, expressives, commissives, and declarations. The study employed a qualitative approach by conducting content analysis on the dialogue of the film ‘Adiwiraku’. The data collected were then categorized according to Searle’s Speech Act Theory. The findings revealed that four types of speech acts are present in the film, which are directives, assertives, expressives, and commissives, while declarations are absent. It is hoped that this study can provide a deeper understanding of how communication functions in everyday life, particularly in social and educational interactions. Understanding speech acts is essential for comprehending the intent behind what is communicated in interactions. Additionally, this study aspires to inspire readers to further explore the pragmatic aspects of communication that involve media, such as films, which often mirror the real-life social interactions and societal dynamics in a country. Keywords: Speech acts, utterances, film, Adiwiraku, Searle’s theory (1969), education Full text: PDF